2021
DOI: 10.55705/cmbr.2021.356664.1057
|View full text |Cite
|
Sign up to set email alerts
|

An introduction on cerebrovascular aneurysms during pregnancy

Abstract: A cerebral aneurysm is an abnormal bulge in the cerebral artery that spreads where the blood vessel wall has weakened. Cerebral aneurysms may allow blood to leak into the subcutaneous space around the brain and cause damage to brain cells. Brain aneurysms can also be ruptured and can lead to serious and possibly fatal strokes. A cerebral aneurysm is known as swelling of a blood vessel in the brain. In the definition of these conditions, it is said that it looks like a hanging berry from a stem. In cases where … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
1
0
0
Order By: Relevance
“…As an indicator of blood clots, this study determined the amount of lupus anticoagulant antibody in the blood of pregnant women. Similar to the results of the studies conducted by other investigators, the level of lupus anticoagulant antibodies has elevated in the blood of aborted women (29)(30)(31)(32)(33)(34).…”
Section: Discussionsupporting
confidence: 87%
“…As an indicator of blood clots, this study determined the amount of lupus anticoagulant antibody in the blood of pregnant women. Similar to the results of the studies conducted by other investigators, the level of lupus anticoagulant antibodies has elevated in the blood of aborted women (29)(30)(31)(32)(33)(34).…”
Section: Discussionsupporting
confidence: 87%
“…Further studies on the relationship between vaginal microecological imbalance and the expression of serum inflammatory factors and GBS infection can provide more effective prevention and treatment strategies for maternal health, and help to improve pregnancy outcomes. Compared with other experimental studies (27)(28)(29)(30)(31), this experiment analyzed the proportion of vaginal microecological imbalance and the expression of serum inflammatory factors in pregnant women with GBS infection and those without GBS infection. It concluded that GBS infection can increase the probability of vaginal microecological imbalance and the expression level of serum inflammatory factors in pregnant women, which will lead to an increase in adverse pregnancy outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In several studies, cellular and molecular aspects of pregnant women have been reported (24)(25)(26)(27).…”
Section: Diagnostic Value Of He Detection By Capillary Electrophoresi...mentioning
confidence: 99%